At stå åbenbart skrifte: Kirketugt og social kontrol i reformationstidens Danmark - Ingesman, Per (Kirkehistoriske Samlinger, 2022)
Summary In 1215, the Fourth Lateran Council made it obligatory for all Christians to confess their sins to their parish priest at least once a year. According to Thomas N. Tentler, the mandatory confession in the medieval Roman Church was an instrument of social control. It intended not only to console worried consciences but also to regulate people’s behaviour. The fact that it was obligatory to go to confession made Martin Luther and other Protestant reformers of the sixteenth century react strongly. It terrorized the consciences, Luther said, to have to perform the correct repentance and make the exhaustive confession that, according to the theologians of the medieval Church, was necessary for the absolution to have effect. Whereas Luther did away with the disciplinary side of the medieval confession, he praised the consoling aspect of it: that you could entrust yourself to and receive consolation from a priest. Therefore, private confession was upheld in the Lutheran churches. This was also the case in Denmark, as the Church Ordinance of 1537/39 shows. In the Church Ordinance, there is a close connection between confession and the Lord’s Supper, the Eucharist. Before you could be handed the sacrament of the altar at Sunday Mass, you had to go to confession. The emphasis, however, was no longer on the individual enumeration of sins committed but instead on demonstrating you had the correct understanding of basic Lutheran doctrines. Since you had to pass such a ‘faith interrogation’ or ‘catechism exam’ to be able to participate in the sacrament, a new variant of the medieval mandatory confession had in fact been introduced. Denying people access to the Lord’s Supper was a first, lenient sanction in the exercise of ecclesiastical discipline. Two other sanctions, public penance and excommunication, would be used in cases of graver sins. This article explores the element of social control connected to ecclesiastical discipline in Reformation Denmark, primarily how people who had committed fornication or adultery were forced to do public penance, i.e. to confess their sins in the presence of the whole congregation – something that was regarded as shameful. The most important source used in the article is a court record book from 1577-1579, which was kept by the cathedral chapter in Lund and contains judgments in marital cases. This hitherto unexplored source shows that the sanctions of ecclesiastical discipline played an important role in the handling of cases of betrothal and marriage. This applies primarily to the requirement to publicly confess one’s sin and receive absolution for it. If either a betrothal or a marriage had been broken by one party while the other was innocent, the innocent party was usually allowed to separate from the partner and marry another. The person who had broken an engagement vow or a marriage, on the contrary, was ordered to confess in public. After this public confession, the person was ordered to remain unmarried until he or she had done pænitentia, i.e. had performed true, visible repentance that had led to an improved way of life. After this, he or she was allowed to re-marry by the ecclesiastical authorities. The cases described in the court record book from Lund are evidence that, in sixteenth-century Denmark, the official social control of the ecclesiastical (and secular) authorities often went hand in hand with the informal social control exercised by family and relatives, neighbours and others in the local community. The parish priest played an important role in the social control that lay in ecclesiastical discipline. It was the parish priest in particular who judged whether people who had broken a betrothal or a marriage, after having confessed their sin in public, had also done pænitentia and could thus be allowed to enter into a new relationship. However, the practice also bears witness to the fact that local lay people, without any encouragement from the authorities, exercised social control themselves – that they kept an eye on each other and perhaps also reprimanded unacceptable sexual behaviour. One of the reasons the ecclesiastical disciplinary sanctions were so successful in getting ordinary people to comply with the authorities’ demands in marital matters is also evidenced by the record book from Lund. In a betrothal or a marriage, there were strong material interests, both at the level of the individual and of the kin: to manage a farm required both a man and a woman, and they had to be married to have legitimate children to whom they could bequeath their farmland and property. At this point, Lutheran marriage ideology suited the social and material needs of agrarian society. It is therefore concluded that, in the small villages and market towns of Reformation Denmark, both the authorities and the local communities were interested in maintaining orderly conditions, particularly in the institution at the very heart of society: the family.